2020
DOI: 10.1007/s13577-019-00319-4
|View full text |Cite
|
Sign up to set email alerts
|

miR-362-5p promotes cell proliferation and cell cycle progression by targeting GAS7 in acute myeloid leukemia

Abstract: Recently, miR-362-5p has attracted special interest as a novel prognostic predictor in acute myeloid leukemia (AML). However, its biological function and underlying molecular mechanism in AML remain to be further defined. Herein, we found that a significant increase in miR-362-5p expression was observed in AML patients and cell lines using quantitative realtime PCR. The expression of miR-362-5p was altered in THP-1 and HL-60 cells by transfecting with miR-362-5p mimic or inhibitor. A series of experiments show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Yang et al validated that GAS5 elevation inhibited viability and facilitated apoptosis of PC cells, and also modulated α‐Solanine‐triggered radiosensitivity 9 . Moreover, it has been reported that upregulated miR‐362‐5p accelerated bladder cancer cell proliferation, 23 and miR‐362‐5p was revealed to promote AML cell proliferation and cell cycle progression 14 . In addition, our in vivo experiment suggested that GAS5 overexpression could decelerate tumor growth in a TC nude mouse model.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Yang et al validated that GAS5 elevation inhibited viability and facilitated apoptosis of PC cells, and also modulated α‐Solanine‐triggered radiosensitivity 9 . Moreover, it has been reported that upregulated miR‐362‐5p accelerated bladder cancer cell proliferation, 23 and miR‐362‐5p was revealed to promote AML cell proliferation and cell cycle progression 14 . In addition, our in vivo experiment suggested that GAS5 overexpression could decelerate tumor growth in a TC nude mouse model.…”
Section: Discussionsupporting
confidence: 54%
“…9 Moreover, it has been reported that upregulated miR-362-5p accelerated bladder cancer cell proliferation, 23 and miR-362-5p was revealed to promote AML cell proliferation and cell cycle progression. 14 In addition, our in vivo experiment F I G U R E 7 GAS5 inactivates the Akt/mTOR signaling pathway by mediating the miR-362-5p/SMG1 axis. (a,b), expression of Akt and mTOR in parent cells and 131 I-resistant TC cells was assessed by Western blot analysis; one-way ANOVA was used for comparisons among multiple groups, followed by Tukey's post hoc test; **, p<.01 suggested that GAS5 overexpression could decelerate tumor growth in a TC nude mouse model.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We identified HBV integrations with high integration allele fraction seven non-recurrent cancer-related genes, including GAS7 [74,75], NS [77,78], NRG1 [79], PRDM16 [80], ARID1B [81], and AFF1 [82]. GAS7 has be directly regulated by P53 and is part of a critical mechanism that mediate metastasis [74]; NRG1 fusions were identified as drivers for lung adenoc…”
Section: Discussionmentioning
confidence: 99%
“…We identified HBV integrations with high integration allele fractions in tumors in seven non-recurrent cancer-related genes, including GAS7 [ 74 , 75 ], NSP [ 76 ], RSPO2 [ 77 , 78 ], NRG1 [ 79 ], PRDM16 [ 80 ], ARID1B [ 81 ], and AFF1 [ 82 ]. GAS7 has been shown to be directly regulated by P53 and is part of a critical mechanism that mediates breast cancer metastasis [ 74 ]; NRG1 fusions were identified as drivers for lung adenocarcinoma [ 79 ]; And the involvement of PRDM16 in leukemia [ 80 ], ARID1B in ovarian cancer [ 81 ], and AFF1 in leukemia [ 82 ] has also been reported; It has been demonstrated that a GAS7 -mediated pathway suppressed proliferation of HCC cells following treatment with oxaliplatin, an alkylating anti-neoplastic agent, and the inhibition of GAS7 negated the beneficial effects of the drug [ 83 ].…”
Section: Discussionmentioning
confidence: 99%